2009
DOI: 10.1210/en.2008-1664
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with the G Protein-Coupled Receptor 30 Agonist G-1 Decreases Blood Pressure in Ovariectomized mRen2.Lewis Rats

Abstract: The mRen2.Lewis congenic strain is an estrogen-sensitive model of hypertension whereby estrogen depletion produces a significant and sustained increase in blood pressure. The recent identification of G protein-coupled receptor 30 (GPR30) as a third estrogen receptor isotype prompted us to test the hypothesis that this novel receptor exhibits beneficial cardiovascular actions in the hypertensive female mRen2.Lewis rat. Intact female, ovariectomized female (OVX), and male mRen2.Lewis rats were treated with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
216
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(234 citation statements)
references
References 32 publications
13
216
4
1
Order By: Relevance
“…[51][52][53] Thus, we considered whether GPER expression would be similarly downregulated in vivo after vascular injury and the consequent shift of VSMCs to the synthetic phenotype. On SDS-PAGE, in carotid artery lysates, GPER was resolved in 2 bands, namely, a major band with a corresponding molecular weight of ≈ 50 kDa-as previously described in other tissues- 54 and a minor band of GPER (≈43 kDa) as reported by other investigators. 55,56 As we have seen in vitro, with VSMC primary culture, after carotid ligation or vascular injury, there was a detectable downregulation of GPER content both with regard to protein content (to 15±6% of control; n=3; Figure 3D) and mRNA content (to 28±3% of control; n=3; Figure 3E).…”
Section: Carotid Injury Leads To An Attenuation Of Gper Expressionsupporting
confidence: 68%
“…[51][52][53] Thus, we considered whether GPER expression would be similarly downregulated in vivo after vascular injury and the consequent shift of VSMCs to the synthetic phenotype. On SDS-PAGE, in carotid artery lysates, GPER was resolved in 2 bands, namely, a major band with a corresponding molecular weight of ≈ 50 kDa-as previously described in other tissues- 54 and a minor band of GPER (≈43 kDa) as reported by other investigators. 55,56 As we have seen in vitro, with VSMC primary culture, after carotid ligation or vascular injury, there was a detectable downregulation of GPER content both with regard to protein content (to 15±6% of control; n=3; Figure 3D) and mRNA content (to 28±3% of control; n=3; Figure 3E).…”
Section: Carotid Injury Leads To An Attenuation Of Gper Expressionsupporting
confidence: 68%
“…Treatment with the selective agonist G‐1 reduces atherosclerosis in ovariectomized mice, and the beneficial effects of GPER in this model are associated with a reduction in macrophage and T‐cell recruitment, indicating an anti‐inflammatory mechanism 55. In addition, activation of GPER has been reported to protect female mice from salt‐ and pressure‐induced vascular damage 56, 57. Altogether, although activation of nuclear, but not membrane, ERα is necessary to induce a protection against atherosclerosis and hypertension, we cannot exclude the participation of other membrane‐initiated steroid signal elicited through GPER‐mediated pathway.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the expression levels of both GPER and HIF-1α were found to be increased in spontaneously hypertensive rat hearts compared to normotensive controls, suggesting that HIF-1α/ GPER signaling may represent a transduction mediator in certain conditions characterized by elevated blood pressure (74), which is tightly linked to hypoxia (82). Of note, the selective GPER agonist G-1 markedly lowered blood pressure in normotensive and hypertensive rats (83,84), thus supporting the hypothesis that GPER may be a valuable pharmacological target for the prevention/treatment of certain cardiovascular diseases. Further supporting the role elicited by GPER in hypoxic conditions, previous studies have reported that its activation may attenuate the detrimental effects induced by oxygen deficiency in some areas of the central nervous system like the hypothalamic-pituitary axis, hippocampal formation, brainstem autonomic nuclei, and spinal cord (85,86).…”
Section: Gper Is Involved In Hypoxia-mediated Signalingmentioning
confidence: 97%